Europe`s new border taxes - Sijbren Cnossen; Erns Verwaal (Center for Economic Studies and ifo Institute (CESifo), 2001)
Instead of abolishing internal border controls in 1993, the European Union (EU) replaced them with VAT and statistical requirements that appear to be just as onerous. For Dutch businesses, the compliance costs of the new requirements are, on average, 5 per cent of the value of their intra-EU trade. This figure is probably higher for other EU Member States. Obviously, the costs constitute a (differentiated) border tax that impedes intra-EU trade. The paper analyses the determinants of the compliance costs, as well as their effect on intra-EU trade intensity. The paper submits that the differential compliance costs violate the non-discrimination provisions of the EC Treaty. Suggestions are made to reduce them.
Keywords: 330